2020
DOI: 10.3390/s20164463
|View full text |Cite
|
Sign up to set email alerts
|

Automotive Radar in a UAV to Assess Earth Surface Processes and Land Responses

Abstract: The use of unmanned aerial vehicles (UAVs) in earth science research has drastically increased during the last decade. The reason being innumerable advantages to detecting and monitoring various environmental processes before and after certain events such as rain, wind, flood, etc. or to assess the current status of specific landforms such as gullies, rills, or ravines. The UAV equipped sensors are a key part to success. Besides commonly used sensors such as cameras, radar sensors are another possibility. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Another digital pressure sensor, BMP388, can also be UAV-embedded with a less sensitive operation range between 300 and 1250 mbar and has a typical relative accuracy of ±0.08 mbar [259]. This BMP388 finds application in UAV automative radar for earth/land monitoring processes [260]. Environmental sensors (a) Pressure sensors A UAV's flight control and navigation are affected by the data provided by the environmental sensors, such as temperature, humidity, and pressure.…”
Section: Sensorymentioning
confidence: 99%
See 1 more Smart Citation
“…Another digital pressure sensor, BMP388, can also be UAV-embedded with a less sensitive operation range between 300 and 1250 mbar and has a typical relative accuracy of ±0.08 mbar [259]. This BMP388 finds application in UAV automative radar for earth/land monitoring processes [260]. Environmental sensors (a) Pressure sensors A UAV's flight control and navigation are affected by the data provided by the environmental sensors, such as temperature, humidity, and pressure.…”
Section: Sensorymentioning
confidence: 99%
“…Another digital pressure sensor, BMP388, can also be UAV-embedded with a less sensitive operation range between 300 and 1250 mbar and has a typical relative accuracy of ±0.08 mbar [259]. This BMP388 finds application in UAV automative radar for earth/land monitoring processes [260].…”
Section: Sensorymentioning
confidence: 99%
“…In this work, we use the ARS 408-21 Long Range Radar 77 GHz Premium (ARS 408-21) sensor, which is an industrial sensor developed by Continental AG. The ARS 400 series of radar sensors was initially developed for the automotive industry and is widely used for automotive applications such as advanced driver assistance systems [6]. As already mentioned, we consider radar data as a point cloud consisting of many radar targets.…”
Section: Sensor Setupmentioning
confidence: 99%
“…For this reason, the use of small, low-cost radar sensors is one of the most incipient priorities in research projects related to geosciences that work within the scope of the automotive field to assess dynamic processes along the Earth's surface at different scales [39,40]. In a previous recent publication [41], it was demonstrated that the installation and use of these sensors is possible and feasible when UAVs are considered. However, the processing of the radar data to obtain a benefit was not shown by these authors.…”
Section: Introductionmentioning
confidence: 99%